Advances in vaccine development and the immune response against toxoplasmosis in sheep and goats - Nishikawa, Yoshifumi; Hasan, Tanjila (Frontiers in Veterinary Science, 2022)
Toxoplasmosis is a zoonotic, parasitic infection caused by the intracellular, apicomplexan parasite Toxoplasma gondii, which infects all homeothermic animals including humans. The parasite has a major economic impact on the livestock industry. This is especially true for small ruminants (sheep, goats) as it is one of the most likely reasons for reproductive disorders in these animals. Primary infection in sheep and goats can result in a fetus that is mummified or macerated, fetal embryonic death, abortion, stillbirth, or the postnatal death of neonates, all of which threaten sheep and goat rearing globally. Humans can also become infected by ingesting bradyzoite-containing chevon or mutton, or the contaminated milk of sheep or goats, highlighting the zoonotic significance of this parasite. This article reviews the advances in vaccine development over recent decades and our current understanding of the immune response to toxoplasmosis in small ruminants (sheep, goats).